MODELING OF DROPLET DYNAMIC AND THERMAL HISTORIES DURING SPRAY FORMING .3. ANALYSIS OF SPRAY SOLID FRACTION - Grant, P; Cantor, B (1995)
The complex equations governing droplet dynamic and thermal behaviour during spray forming have been analysed to give an approximate expression for the spray solid fraction as a function of the process parameters of the form fS = a1 + a2 Δ T + a3 frac(υg i z2 / 3, over(M, ̇)1 / 2) where vgi is the initial gas velocity at atomisation, Ṁ is the molten alloy mass flow rate, ΔT is the molten alloy super heat above the liquidus, and z is the axial distance. This expression provides an extremely convenient relationship to indicate the variation of spray solid fraction during spray forming, which is a key variable controlling final as sprayed billet microstructure. Predicted N2 atomised Al-4 wt%Cu spray solid fractions based upon the analytical expression have been compared with equivalent results obtained from a detailed computer model described previously in Parts I and II under a wide range of conditions of vgi, Ṁ, ΔT and z and gave good agreement. Best-fit values of a1, a2 and a3 were 1.9 × 10-1, -1.4 × 10-3 and 1.3 × 10-3 respectively, in good agreement with predicted values. © 1995 Elsevier Science Ltd.